2022
DOI: 10.1111/jvh.13708
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C hospitalizations in Spain and impact of new curative antiviral therapies

Abstract: Chronic hepatitis C virus (HCV) infection is major cause of decompensated cirrhosis and liver cancer. The advent of curative new antiviral therapies since year 2015 has dramatically improved the prognosis of HCV patients. The real‐life clinical benefits at country level of these therapies have not yet been assessed. This is a retrospective study of all hospitalizations in Spain including HCV as diagnosis using the Spanish National Registry of Hospital Discharges. Information was retrieved from 1997 to 2019. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It is noteworthy that in-hospital mortality in HBV patients is similar to the death rate in patients admitted with other hepatitis viruses, such as hepatitis C or hepatitis delta. 15,27 It may reflect that once the end-stage liver disease has developed, outcomes in patients with distinct viral hepatitis aetiologies do not differ much.…”
Section: Hepatitis B Hepatitis Deltamentioning
confidence: 99%
“…It is noteworthy that in-hospital mortality in HBV patients is similar to the death rate in patients admitted with other hepatitis viruses, such as hepatitis C or hepatitis delta. 15,27 It may reflect that once the end-stage liver disease has developed, outcomes in patients with distinct viral hepatitis aetiologies do not differ much.…”
Section: Hepatitis B Hepatitis Deltamentioning
confidence: 99%
“…The introduction of direct acting antivirals (DAAs) in 2014 lay the foundation for reducing the morbidity and mortality of HCV infections, e.g., by reducing liver decompensation events among hospitalized patients diagnosed with hepatitis C ( 10 ). Several DAA substances have been registered and approved in Germany, and since 2017 single-tablet pan-genotypic combination treatments are available ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…This reduction was primarily caused by a fall in liver decompensation events. [ 2 ] However, DAA therapy was significantly affected since the onset of COVID‐19, and the pandemic outbreak was associated with a sharp decrease in DAA prescription dispensing, with levels of dispensing remaining below their prepandemic baseline in April 2021. [ 3 ] Doubtless, outcomes of HCV‐related cirrhosis could have been severely affected in the COVID‐19 era.…”
mentioning
confidence: 99%
“…I commend the authors for undertaking such a rigorous study and would like to share my suggestions on the potential confounders affecting the outcomes.First, this study's etiologies of liver cirrhosis were not shown in detail. [1] HCV infection is a major cause of liver cirrhosis [2] ; hospital admissions of patients with HCV have significantly declined in Spain since 2015 following a wide prescription of oral direct-acting antivirals (DAAs). This reduction was primarily caused by a fall in liver decompensation events.…”
mentioning
confidence: 99%
See 1 more Smart Citation